Procedure manual for application of duty remission regulations - EAC (EAC, 2014)
This Manual is an East African Community publication which sets out guidelines on operationalisation of the duty remission scheme as set out in the EAC Customs Duty Remission Regulations, 2008 made under the EAC Customs Management Act, 2004, and the Protocol on the Establishment of the EAC Customs Union. The manual spells out in detail the duties of the Duty Remission Committees, the processing of applications for duty remission and administration of duty remission.
Keywords: Duty Remission regulation; Customs Duty; Customs Union